Reproduction of contagious bovine pleuropneumonia via aerosol-based challenge with Mycoplasma mycoides subsp. mycoides - Sacchini, F.; Liljander, Anne M.; Heller, M.; Poole, Elizabeth J.; Posthaus, H.; Schieck, Elise G.; Jores, Joerg (Springer, 2020)
Contagious bovine pleuropneumonia (CBPP) is a respiratory disease caused by Mycoplasma mycoides subsp. mycoides. Infection occurs via Mycoplasma-containing droplets and therefore requires close contact between animals. The current infection models are suboptimal and based on intratracheal installation of mycoplasmas or in-contact infection. This work tested the infection of adult cattle via aerosols containing live mycoplasmas mimicking the infection of cattle in the field. Therefore, we infected six cattle with aerosolized Mycoplasma mycoides subsp. mycoides strain Afadé over seven consecutive days with altogether 109 colony forming units. All animals seroconverted between 11–24 days post infection and five out of six animals showed typical CBPP lesions. One animal did not show any lung lesions at necropsy, while another animal had to be euthanized at 25 days post infection because it reached endpoint criteria. Seroconversion confirmed successful infection and the spectrum of clinical and lesions observed mirrors epidemiological models and the field situation, in which only a fraction of animals suffers from acute clinical disease post infection.